Prevalence and Factors Associated with Antepartum Depression: A University Hospital-Based - Choosuk, Pavarisa; Pitanupong, Jarurin; Suwanrath, Chitkasaem (Siriraj Medical Journal, 2021)
Objective: This study aimed to assess the prevalence of and factors associated with antepartum depression among Thai women. Materials and Methods: All pregnant women attending the Antenatal Care Clinic at Songklanagarind Hospital from June to August 2020 were invited to participate and evaluated through self-administered questionnaires. Multivariate logistic regression models were used for the data analysis in order to control for potential confounders. Results: 435 women were in their first, second, and third trimester of pregnancy (20.2 %, 39.5 %, and 40.2 %, respectively). The majority of them reported normal Rosenberg’s Self-esteem Scale scores (83.4 %) and a high level of perceived social support (74.5 %). Moreover, according to the Edinburgh Postnatal Depression Scale (EPDS) scores, the prevalence of antepartum depression was 10.6 %. A multivariate logistic regression analysis showed that factors associated with antepartum depression were second trimester of pregnancy, survival and below-survival levels of income, unintended pregnancy, and low level of self-esteem. Conclusion: One-tenth of pregnant Thai women suffered from depression. Advanced gestational age, low income, unintended pregnancy, and low self-esteem were significant factors associated with antepartum depression.